Exposures and hearing thresholds in music students due to training sessions - JAROSZEWSKI, A.; FIDECKI, T.; ROGOWSKI, P. (Archives of Acoustics, 1999)
Measurements of SPL’s in sound emission from some wind instruments during training sessions of music students show all in excess of LAmax 110 dB and reach LAmax 132 dB in some cases. Long time average spectra in 1/3-octave bands and cumulative distribution functions show that e.g. sound pressure levels LA 50 are often around 100-110 dB and in most instruments the spectra cover substantial range of frequencies. Resting hearing thresholds in many students show dips of various depths at 6 kHz, which in some cases reach over 30 dB. TTS2 measured at 6 kHz following 4-hrs training session reach 40 dB.